Measles outbreak investigation in Buah health district, Grand Kru County, Liberia, February-April 2020 - Francis Bobway; Faith Tina Whesseh; Chukwuma David Umeokonkwo; Obafemi Joseph Babalola; Jimmy Lawubah; Himiede Wede Seysay; Lily Sanvee-Blebo; Boye Nuyelleh; Maame Amo-Addae (Journal of Interventional Epidemiology and Public Health)
Introduction: Measles is a highly contagious illness and remains one of the leading causes of death of children worldwide. Measles is one of the epidemic-prone diseases for weekly reporting in the revised Integrated Disease Surveillance and Response in Liberia. In 2020, Liberia reported a total of 623 measles cases, of which, Grand Kru County accounted for 28.6%. We present the epidemiological characterization of the measles outbreak in Grand Kru County in 2020.